Local approaches to climate-sensitive peacebuilding: lessons from Afghanistan. Issue 1 (14th June 2022) - Abdenur, Adriana E.; Tripathi, Siddharth
Abstract : Since the early 2010s, academic and policy debates about the interlinkages between climate and security have expanded and deepened. Climate is now widely acknowledged to magnify security risks especially in conflict or post-conflict contexts. This relationship is viewed as complex, dynamic and indirect, involving a wide range of intermediate variables. However, this discussion – and hence, related policy efforts – have tended to occur at highly aggregate levels of analysis, especially national, regional and global ones. Instead, this paper addresses climate-sensitive peacebuilding at the local level. What does local climate-sensitive peacebuilding look like on the ground? What are the promising areas for research and policy responses in fragile and conflict-affected settings? After offering a broad overview of climate-sensitive peacebuilding, we focus on the case of Afghanistan, drawing on specific examples that were in place prior to the 2021 return to power of the Taliban. We find that the traditional Western approach in the country – top-down, focused on hard security rather than human security and highly state-centric – tends to ignore the impacts of climate change. In addition, the dominant security paradigm overlooks the potential of local peacebuilding initiatives that address adaptation and resilience. We argue that climate-sensitive peacebuilding offers a bottom-up alternative to addressing the intersection of these risks in conflict-affected settings.